The Palgrave Macmillan dictionary of political thought - Scruton, Roger (Palgrave Macmillan, 2007)
"A profound and incisive guide to political ideas. This new edition takes stock of the revolutionary political changes that have taken place since the dictionary was first published in 1982, bringing the dictionary up to date"--Publisher's description